Reflections on Ijtihad and Moderate Islam - Louay Safi (International Institute of Islamic Thought, 2005)
My remarks focus on two central themes addressed in the preceding debate: moderate Muslim and ijtihad. Although my assignment requires me to engage the five illustrious interlocutors, I have chosen to refer to salient aspects of their statements, particularly those that help in clarifying the two themes alluded to above. Given the brevity of my remarks and the limited space allocated to comments, it is not possible to expound on the epistemological and ontological underpinnings of the arguments. The following arguments, therefore, take the form of a number of assertions that lack theoretical grounding. This will be felt particularly by readers who do not share the basic assumptions upon which the arguments are premised. But, I guess this is exactly what the editor has intended: to explore diverse views within and without the Muslim community. Still, this intellectual exercise provides an important backdrop for the current debate about the significance of Islam in the profound transformations occurring in contemporary Islamic thinking. I also believe that the debate reveals the complexity of the process of Islamic reform and diversity of its forms and manifestations. Moderate Islam “Moderate Islam” has become a most contentious term, as the debate above shows. The word moderate is frequently used in reference to the political centrist: “A person who takes a position in the political center.” Amoderate is a person who is neither on the extreme left nor on the extreme right of the political, moral, or religious spectrum of ideas. Defining moderate becomes tricky when one takes a historical view of mainstream society. From a historical point of view, the terms moderate and extremist immediately loose their absolutist standing and acquire a ...